2009
DOI: 10.1111/j.1365-2745.2009.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant genetic diversity yields increased plant productivity and herbivore performance

Abstract: Summary1. Plant genotypic diversity has important consequences for a variety of ecosystem processes, yet empirical evidence for its effects on productivity, one of the most fundamental of these processes, is lacking. In addition, the performance of insect herbivores in response to high genotypic diversity is unknown, despite previous work demonstrating differential herbivore performance among plant genotypes. 2. We manipulated genotypic diversity of the annual plant Arabidopsis thaliana in both the presence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 51 publications
1
99
2
2
Order By: Relevance
“…Inconsistent with recent studies about the positive relationship of plant productivity and plant cultivar diversity (Hughes et al, 2008;Kotowska et al, 2010), no significant effect of plant cultivar diversity on plant biomass was detected in our study. van Ruijven and Berendse (2005) found that positive species richnessproductivity relationships strengthened over time in perennial plant communities through increased nutrient use efficiency, both spatially and temporally.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Inconsistent with recent studies about the positive relationship of plant productivity and plant cultivar diversity (Hughes et al, 2008;Kotowska et al, 2010), no significant effect of plant cultivar diversity on plant biomass was detected in our study. van Ruijven and Berendse (2005) found that positive species richnessproductivity relationships strengthened over time in perennial plant communities through increased nutrient use efficiency, both spatially and temporally.…”
Section: Discussioncontrasting
confidence: 70%
“…However, resistance effects can depend on the chosen cultivars, as Wolfe (1985) illustrated. Kotowska et al (2010) also found that leaf herbivory was more severe in populations with high plant cultivar diversity and argued that this was due to their high productivity. In our study, we did not find a difference in plant productivity between communities of different cultivar diversity, making this mechanism unlikely here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea plays a key role in hypotheses for the evolution of sex [3,4] and outcrossing [5] and has received some support in plant ecology (e.g. [6][7][8] and references therein).…”
Section: Introductionmentioning
confidence: 99%